As competências interagência do trabalhador na indústria 4.0: um estudo de literatura - Mazine, Bruna Alice (2023)
Each Industrial Revolution is seen as a huge process of technological transformation that ended up in the industry 4.0 which has transformed the way the world is organized. Focusing in the interaction between human and machine, the 4th Industrial Revolution as brought the need of new professional skills. In this sense, the present work has the goal of identifying the main inter-agent skills needed to form the professional’s profile in the industry 4.0 according to the analysis of the main papers of this area, using a base of 24 articles previously chosen. This work of gathering and organizing the data seeks to assist in the understanding of the equirements for the workers in the industry 4.0. As conclusion, this work shows three most relevant skills for these professionals: Collaboration, Human-machine Interface and Interdisciplinarity.